Perceptions about English as second language teachers’ technology based English language teaching in Pakistan: Attitudes, uses of technology and challenges - Abbasi, Wajahat Taj; Ainol Haryati, Ibrahim; Fatimah, Ali (Springer Science and Business Media Deutschland GmbH, 2022)
This study aims to find out the perceptions of English as a second language (henceforth, ESL) teachers’ attitudes towards the use of technology for teaching of English to the undergraduate students in Pakistan. The study exposes the uses of information and communication technologies (henceforth, ICT) in teaching, and the difficulties faced in integrating technology for teaching of English. Data is collected through survey questionnaire and interview protocol from ESL teachers teaching at college level in Abbottabad, Pakistan. Survey data is analyzed through SPSS 22 while interview questions have a thematic analysis. Findings of survey and interview protocol used in the study reveal positive attitudes on the part of teachers towards the use of technology. No significant difference is found among teachers’ use of technology due to gender or academic qualification. However, the difference between teachers’ technology use can be ascribed to their competence. The use of technology is beneficial for teaching and learning environment, but its’ use is not optimal in educational environment in Pakistan. The findings highlight limited use of technology due to shortage of resources, unavailability of tools and lack of training. The study puts forward some recommendations for the effective use of technology in language teaching and the removal of the potential barriers in its use by teachers in Pakistan.